Housing design for residential livability: the low-income earner perspective - Bashari, Sunusi; Hashim, Ahmad Hariza (Readers Insight Publisher, 2019)
In Nigeria, statistics has shown that over 7 out of every 10 people live below the minimum poverty level and 9 of every 10 are in the low-income group (Fadairo & Olotuah, 2013). This indicates that, these people cannot provide housing for themselves, they need intervention from government through public low-cost housing. Public Low-cost housing has been defined as constructed public residential houses funded by the government or in partnership with the government under the public-private partnership (PPP) scheme, to provide affordable housing for low-income people (Ayoola & Amole, 2014; Makinde, 2014a). The results indicated that, there is need to consider users preferences in construction of public low-cost housing so as achieve maximum satisfaction.